Corrosion of high strength pipeline steel weldment using submerged jet impingement. - Nofrizal (Cranfield University, 2019)
The aim of this research is to evaluate submerged jet impingement (SJI) as a tool for assessing the effect of flow and the associated corrosion behaviour across an X65 high strength pipeline weldment. The focus is corrosion caused by turbulent artificial sea water at different velocities impinging onto the weldment. An SJI target consisting of 3 rings (centre, inner and outer) based on a previous design [13], was constructed from an X65 pipeline steel weldment. Parent material (PM), heat affected zone (HAZ) and weld metal (WM) are analysed together in a high shear stress environment and changes in the weldment in a range of hydrodynamic conditions evaluated. Electrochemical measurements were performed with X65 pipeline steel with stagnant and flowing artificial seawater saturated with carbon dioxide at 1 bar at 0 -10 m/s at 25˚C and pH 4. The behaviour with and without an inhibitor was also examined. Galvanic current characteristics between coupled weldment regions were recorded using a zero-resistance ammeter (ZRA), and self-corrosion analysed using linear polarisation resistance (LPR) measurements. Computational fluid dynamic (CFD) analysis was undertaken to understand the hydrodynamic effects and velocity changes across the SJI target in flowing conditions. The velocity distribution across the target varied in each weld region where the centre, outer and inner electrodes are 25, 33 and 50% of the impinging jet velocity respectively. The inner electrodes of the SJI target experience 30% of the expected wall shear stress calculated from the impinging jet velocity. Alternative SJI target configurations are proposed to represent a wide range of shear stress and fluid velocities across the target with good precision and accuracy. For low turbulence, the target centre electrode is minimised or placed at the target edge. To achieve maximum turbulence, an electrode 4 mm from the target centre is proposed. To achieve 10 m/s on the suggested target, a jet velocity of just over 15 m/s is required.
Keywords: Submerged jet impingement; preferential weld corrosion; X65 carbon steel; inhibitor; carbon dioxide; heat affected zone